2008
DOI: 10.1308/003588408x285757
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Management of Malignant Acute Left-Sided Colonic Obstruction

Abstract: The searches showed one Cochrane systematic review, two further systematic reviews, one meta-analysis, two decision METHODS A literature search was undertaken using PubMed and the Cochrane Library regarding the options in emergency management of left-sided colonic obstruction focusing on outcomes such as mortality, morbidity, long-term prognosis and cost effectiveness. DISCUSSION Colonic stenting is the best option either for palliation or as a bridge to surgery. It reduces morbidity and mortality rate and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 42 publications
(63 reference statements)
0
54
0
14
Order By: Relevance
“…[5] Emergent surgery in colorectal cancers has been reported to be associated with high mortality and morbidity rates. [6,7] Several surgical procedures have been described for the treatment of obstructive lesions of the left colon; however, there is no consensus on a particular method to be used for the surgical management of acute obstructions due to malignancies. [8,9] The classical three-step surgical approach including initial transverse loop colostomy followed by left colectomy performed after improvement in the patient's general status and closure by colostomy after two or three weeks has started to be replaced with the more aggressive single-step emergent surgery as subtotal colectomy and primary anastomosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Emergent surgery in colorectal cancers has been reported to be associated with high mortality and morbidity rates. [6,7] Several surgical procedures have been described for the treatment of obstructive lesions of the left colon; however, there is no consensus on a particular method to be used for the surgical management of acute obstructions due to malignancies. [8,9] The classical three-step surgical approach including initial transverse loop colostomy followed by left colectomy performed after improvement in the patient's general status and closure by colostomy after two or three weeks has started to be replaced with the more aggressive single-step emergent surgery as subtotal colectomy and primary anastomosis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that intraoperative colonic lavage prolongs operative duration and does not lower the incidence of anastomosis leak. [7] Intraluminal fecal loading and the difference between the proximal and distal colon diameters renders difficulty in terms of anastomosis technique in patients treated by resection and primary anastomosis. [26,27] An increased incidence of anastomosis leak, which is the most significant disadvantage, has currently been reported within 1-7% in several studies, and the mortality rate has been reported to be 2-9%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Kolon malign obstrüksiyonlar›n›n büyük ço¤unlu¤u (%65-90) sol kolon kaynakl› tümörlere ba¤l›d›r. 3,5,6 Serimizde bu oran %86 olup literatür ile benzerdir.…”
Section: © Tkrcd 2011unclassified
“…В таких слу-чаях систематический анализ эффективности исполь-зования колоректальных стентов позволяет предполо-жить, что они являются относительно безопасным и действенным симптоматическим средством [16,17]. Однако для применения противопоказаний для уста-новки стента необходимо выполнение компьютерной томографии брюшной полости [18][19][20] для выявления возможных перфораций ТК, некроза опухоли, пара-колитического абсцесса [21,22].…”
unclassified